Development of A New HPLC Method for Separation and Determination 25(OH)- Cholecalciferol (Vitamin D3(. - et.al, Prof. Dr. Sarmad B. Dikran (Al-Qadisiyah Journal of Pure Science, 2017)
Vitamin D3 was found interference with other fat soluble vitamins (especially vitamin A and E) that are commonly present with vitamin D, in Serum & pharmaceutical preparation. In the present study, a rapid, simple and economical reversed phase-HPLC procedure has been fixed optimization of condition and developed for the separation and determination of vitamin D3 in mixture standard of Vitamin D3and Vitamin A. Anew method were developed in HPLC,based method with a UV detector by examining various conditions including mobile phase, flow rate, volume inject and temperature, we have also proposed a very simple method of isolation of these vitamins. The vitamins were separated isocratic ally on a Knauer C18 column (250Ã—4.6mm, 5Î¼m particle size) with a mobile phase consisting of isocratic acetonitrile and methanol (75:25, v/v) operated at 40ÂºC with retention times less than 10 min. and the detection limit of our developed HPLC method is 0.01Î¼g/ml. The eluted vitamins were identified and monitored on a UV-Detector at 265 nm with optimum flow rate 1.5 mL/min and 50Î¼L Injection volume.